Effect of combined treatment with insulin, metformin, and gliclazide on the expression and activity of Akt, mTOR, and p70S6K protein kinases in lymphocytes of diabetic patients - Sokolova, L.K.; Pushkarev, V.M.; Belchina, Yu.B.; Pushkarev, V.V.; Vatseba, T.S.; Tronko, M.D. (Reports of the National Academy of Sciences of Ukraine, 2018)
The expression of the main effector protein kinase Akt of the PI3K signaling pathway and the activities of mTOR and p70S6K protein kinases in lymphocytes of patients with diabetes mellitus are determined at the combination treatment with insulin and hypoglycemic drugs. It is shown that the Akt expression is reduced in blood mononuclear cells of patients with diabetes of the 2nd and, to a less extent, type 1. The activities of mTOR and p70S6K are also reduced in lymphocytes of patients with type 2 diabetes. Possible mechanisms of inhibiting the expression and activity of protein kinases are discussed.